The Influence of Product Quality, Price, and Halal Label on Consumer Purchasing Decisions on Wardah Cosmetics - Hamzan Wadi; Baiq Solatiyah (Program Studi Ekonomi Islam Fakultas Ekonomi Universitas Nahdlatul UlamaNusa Tenggara Barat, 2023)
Women have different needs from men, therefore women are a very potential market segmentation for various needs, one of which is cosmetics. Women are very concerned about their appearance, in contrast to men who are more likely to ignore appearance if they don't want to going out, but women pay attention to appearance both in a state of wanting to going out or in a state of not wanting to going out. Companies must be able to compete in the current era so that companies must innovate, promote, and evaluate so that companies can know the desires of the changing market. The purpose of this study was to find out whether product quality, price and halal labels affect consumer purchasing decisions on Wardah cosmetics. This research is a research with a quantitative approach with survey methods. The population in this study is consumers of Wardah cosmetics in the city of Mataram whose population number is not counted so that the population number is not known with certainty. The sampling technique uses purposive sampling with respondents in this study are 100 people. The data collection technique in this study is by using a questionnaire with the help of google from then processed using SPSS 16.0. The analysis methods used are validity and reliability tests, classical assumption tests, multiple linear regression tests, hypothesis tests through t tests and f tests, and determination coefficient tests (R2). The results showed that: (1) there was no partial influence of product quality variables on purchasing decisions as evidenced by the tcount < ttable (-1.383 < 1.988). (2) There is a partial influence of price variables on purchasing decisions as evidenced by the tcount > ttable (14,869 > 1,988). (3) There is no influence of halal label variables on purchasing decisions as evidenced by the tcount <ttable (-1.847 < 1,988). Keywords: Product Quality, Halal Label, Price, Purchasing Decision Women have different needs from men, therefore women are a very potential market segmentation for various needs, one of which is cosmetics. Women are very concerned about their appearance, in contrast to men who are more likely to ignore appearance if they don't want to going out, but women pay attention to appearance both in a state of wanting to going out or in a state of not wanting to going out. Companies must be able to compete in the current era so that companies must innovate, promote, and evaluate so that companies can know the desires of the changing market. The purpose of this study was to find out whether product quality, price and halal labels affect consumer purchasing decisions on Wardah cosmetics. This research is a research with a quantitative approach with survey methods. The population in this study is consumers of Wardah cosmetics in the city of Mataram whose population number is not counted so that the population number is not known with certainty. The sampling technique uses purposive sampling with respondents in this study are 100 people. The data collection technique in this study is by using a questionnaire with the help of google from then processed using SPSS 16.0. The analysis methods used are validity and reliability tests, classical assumption tests, multiple linear regression tests, hypothesis tests through t tests and f tests, and determination coefficient tests (R2). The results showed that: (1) there was no partial influence of product quality variables on purchasing decisions as evidenced by the tcount < ttable (-1.383 < 1.988). (2) There is a partial influence of price variables on purchasing decisions as evidenced by the tcount > ttable (14,869 > 1,988). (3) There is no influence of halal label variables on purchasing decisions as evidenced by the tcount <ttable (-1.847 < 1,988).